Enhancing Mathematical Comprehension through Technology: A Systematic Literature Review on the Effectiveness of Mathematics Software - Dina Fakhriyana; Nelly Mukhibbatunni’mah; Muhammad Rifqi Asshofi; Tsalisa Zidna Ifthoriya (Universitas Negeri Surabaya, 2026)
The role of educators in designing effective learning media is crucial to address students’ difficulties in mathematics, particularly the lack of engagement and limited integration of technology in the learning process. This study aims to fill this gap by systematically reviewing the use of mathematics software in enhancing mathematical comprehension, focusing on identifying the types of software, analyzing their effectiveness in supporting improved mathematical comprehension, and examining factors that influence their use. A qualitative Systematic Literature Review (SLR) approach was employed, with data collected using the Publish or Perish application based on the Google Scholar database. From 747 articles published between 2020 and 2024, 27 relevant articles were selected for analysis after applying exclusion criteria. The findings identified eight types of mathematics software commonly used in learning, namely GeoGebra, Construct, Cabri 3D, Wingeom, Autograph, Maple, Geometer’s Sketchpad, and SageMath. These software programs were found to be effective in enhancing mathematical comprehension through interactive visualizations, independent exploration, and active learning processes. Their effectiveness, however, depends not only on technological sophistication but also on instructional design, collaboration, and learning methods employed by educators. The results imply that integrating mathematics software into teaching can significantly improve students’ conceptual comprehension and overall learning quality. Future research is encouraged to examine contextual factors such as infrastructure, teachers’ skills, and students’ readiness, as well as to explore impacts on non-cognitive aspects like motivation, attitudes, and critical thinking, while also developing valid evaluation instruments for measuring comprehension improvement.